Why Stock Returns on Property and Real Estate Companies on BEI? - Isnaeni Rokhayati; Herwiek Diyah Lestari; Harsuti Harsuti; Winda Rosadi (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This study aims to analyze the effect of return on equity, price earning ratio and net profit margin on stock returns. The dependent variable in this study is stock return. While the independent variables are return on equity, price earning ratio and net profit margin. The population in this study are property and real estate sector companies listed on the Indonesia Stock Exchange during 2015-2019. The samples obtained were 28 companies using purposive sampling method. The analytical tool used is panel data regression analysis with the help of the software program Eviews 10. Using the fixed effects model, the results show that the return on equity and price earning ratio variables have a significant positive effect on stock returns. While the net profit margin has no effect on stock returns. These results indicate that the stock return of the property and real estate sector companies will change, which is influenced by the return on equity variable and the price earning ratio variable. The implication of this research is that the company is expected to increase revenue by managing or utilizing the capital owned by the company, increasing total sales and minimizing expenses so that the company gets an increasing stock return.